Kebiasaan Makan dan Luas Relung Ikan-Ikan Indigenous yang Ditemukan di Waduk Penjalin Kabupaten Brebes, Jawa Tengah - . Elinah; Djamar Tumpal Floranthus Lumban Batu; Yunizar Ernawati (Jurnal Ilmu Pertanian Indonesia, 2016)
Knowledge about food habits it is need to see how fish utilize their resources. The objective of this study was to assess feeding habits and niches breath fish species indigenous at Penjalin reservoir. This study was conducted during three months from Maret-Mei 2015. Location of the study were divided into 4 stations and sampling was conducted using gill nets. Feeding habits analysis used of the index of preponderance whereas calculation the niche breath using the method of Levin's Measure. In general, the niches breath of indigenous fish in the Penjalin reservoir ranged between 0.71-3.92. The result showed that uceng (Nemacheilus fasciatus), benteur (Puntius binotatus), and wader padi (Rasbora lateristriata) classified as more freely of other indigenous fish species, because it is able to utilize several different resources as a main food. Selective trait shown by (Dermogenys pusilla) because only use one kind of natural food with a high percentage.